A Shared Warp: The Woven Belts of the Lao Han People, China - Celia Elliott-Minty (EXARC, 2021)
The remote mountain area of Guizhou in southwest China is ethnically diverse, and interesting textile traditions survive among the groups. Perhaps the best known are the multicoloured costumes of the Miao people that are skilfully decorated with embroidery and braids (Smith, 2007). Another ethnic group are the "Lao Han" (the ancient Han Chinese) who consider themselves unique from the rest of the majority Han population of China as a whole. They have lived in the Guizhou region since at least the 14th century CE when they were sent there as soldiers on military campaigns. Many stayed and took minority women as wives and formed separate communities. They are also known as the Chuanlan (Blue Dressed people) and are among the many ethnic groups in Guizhou province not officially recognised (Wikipedia, 2020; Joshua Project, 2020). Traditional costume has survived in the isolated Lao Han villages, especially amongst the women. Part of their costume includes a very long handwoven belt that incorporates two different weaving techniques on the same warp and is finished with a complex knotted tassel at each end. The belt begins and ends with a tube that is woven in a tabby weave, whereas the middle section has one or two textured areas that are achieved by using hexagonal weaving tablets in an unusual way.